2009
DOI: 10.1016/j.jpcs.2008.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of Si nanocrystals under selective excitation

Abstract: Photoluminescence of Si nanocrystals passivated by different alkanes (hexane, octane, and tridecane) was studied at room temperature. It is shown that the emission band shape is not affected by the length of the carbon chain in the alkanes used for passivation. A pronounced fine structure of the photoluminescence band consisting of peaks separated by 150-160 meV was observed under resonant excitation. The structure is interpreted by predominant contribution from Si nanocrystal groups with particular stable siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
3
11
0
3
Order By: Relevance
“…20 Moreover, many PL experiments demonstrated that only a very small fraction of the NCs in the samples contributes to the observed PL, enforcing the idea that precise structural conditions are required in order to achieve high emission rates. [24][25][26][27] Finally, recent calculations reported especially high optical yields for small NCs, 28 , enhancing the weight held by their contribution in real samples. It is therefore clear the importance of understanding the factors that, at these sizes, contribute to enhance (or reduce) the NC optical response.…”
Section: Introductionmentioning
confidence: 97%
“…20 Moreover, many PL experiments demonstrated that only a very small fraction of the NCs in the samples contributes to the observed PL, enforcing the idea that precise structural conditions are required in order to achieve high emission rates. [24][25][26][27] Finally, recent calculations reported especially high optical yields for small NCs, 28 , enhancing the weight held by their contribution in real samples. It is therefore clear the importance of understanding the factors that, at these sizes, contribute to enhance (or reduce) the NC optical response.…”
Section: Introductionmentioning
confidence: 97%
“…24,25,28 The treatment of single NCs with atomiclike models allows a comparison between the collective response of a sample with the sum of the responses of the individual NCs, leading to useful information about the NC-NC interaction mechanisms. Also, many works have already indicated the predominant contribution from Si NC with particular size/shape, 27,29,30 providing important implications for the identification of the best conditions for light emission and optical gain.…”
Section: Introductionmentioning
confidence: 99%
“…Donde F corr es la intensidad de fluorescencia real; F obs es la intensidad de fluorescencia registrada por el equipo y A es la absorbancia de la muestra. [Dobrovolskas 2009, Holmes 2001 y pueden ser atribuidos a dos factores. El primero de ellos es la contribución de poblaciones de nanopartículas con un número especifico de átomos y configuración superficial [Dobrovolskas 2009].…”
Section: Calibración Del Espectrofluórometro Y Corrección Por Filtro unclassified
“…[Dobrovolskas 2009, Holmes 2001 y pueden ser atribuidos a dos factores. El primero de ellos es la contribución de poblaciones de nanopartículas con un número especifico de átomos y configuración superficial [Dobrovolskas 2009]. El segundo factor se atribuye a la presencia de oxigeno en la superficie de las partículas [Holmes 2001].…”
Section: Calibración Del Espectrofluórometro Y Corrección Por Filtro unclassified
See 1 more Smart Citation